Manhaj Tarjih Muhammadiyah: Perspektif, Sumber, Pendekatan, dan Prosedur Teknis - Safitrianingsih; Sumiyati; Amaliyatul Fitriyah; Nurul Hayati; Heri Rifhan Halili (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study examines the Manhaj Tarjih of Muhammadiyah, a methodological framework developed to guide Islamic legal reasoning and decision-making, by exploring its perspectives, sources, approaches, and technical procedures in order to elucidate its epistemological foundations and contemporary relevance. Employing a library research design and a content analysis approach, the study analyzes primary sources issued by the Majelis Tarjih and official Muhammadiyah publications, alongside secondary academic interpretations. The findings indicate that the Manhaj Tarjih of Muhammadiyah integrates classical Islamic jurisprudence with rational and contextual considerations, positioning the Qur’an and Sunnah as the primary sources while also recognizing ijmāʿ, qiyās, and contemporary ijtihād. The study identifies a distinctive methodological synthesis that balances textual authority with the demands of social reform through an integrative approach combining bayānī (textual), burhānī (rational), and ʿirfānī (spiritual) epistemologies. Theoretically, this research contributes to the discourse on Islamic legal methodology by offering a contextual framework adaptive to modern challenges, while practically it provides guidance for scholars, educators, and Islamic policymakers in applying religious reasoning that remains faithful to revelatory sources yet responsive to contemporary realities, thereby positioning the Manhaj Tarjih of Muhammadiyah as a dynamic and reformist paradigm in Islamic thought and underscoring Muhammadiyah’s role as a progressive Islamic movement within the global landscape of Islamic scholarship.